1990
DOI: 10.1097/00004032-199010000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Ca and Sr in Late Adult Life

Abstract: Data are presented on the metabolism of Ca and Sr in a healthy male volunteer who, in a series of investigations conducted between the ages of 53 and 82 y, received controlled intakes of 45Ca, 47Ca, or 85Sr. No age-related trends were established, either in factors affecting the skeletal deposition of the tracers or in their subsequent retention studied for up to 462 d after intake. The data thus lend support to an important working postulate in the ICRP's model of alkaline earth metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
3
12
0
1
Order By: Relevance
“…In three healthy subjects that received a single oral dose of SrCl 2 , the estimated average wholebody elimination half-times, estimated over 13 days, were 2 (30%) and 59 days (70%) (Uchiyama et al 1973). Similar short-term rates of elimination have been observed within days to a few weeks after an intravenous injection of SrCl 2 (MacDonald et al 1965;Newton et al 1990). …”
Section: Oral Exposuresupporting
confidence: 65%
See 2 more Smart Citations
“…In three healthy subjects that received a single oral dose of SrCl 2 , the estimated average wholebody elimination half-times, estimated over 13 days, were 2 (30%) and 59 days (70%) (Uchiyama et al 1973). Similar short-term rates of elimination have been observed within days to a few weeks after an intravenous injection of SrCl 2 (MacDonald et al 1965;Newton et al 1990). …”
Section: Oral Exposuresupporting
confidence: 65%
“…The urine:fecal excretion ratio of 3 that was observed in the radium dial workers is consistent with ratios of 2-6 observed several days to weeks after subjects received an intravenous injection of SrCl 2 (Bishop et al 1960;Blake et al 1989aBlake et al , 1989bLikhtarev et al 1975;Newton et al 1990;Samachson 1966;Snyder et al 1964;Uchiyama et al 1973). Thus, urine appears to be the major route of excretion of absorbed strontium.…”
Section: Oral Exposuresupporting
confidence: 64%
See 1 more Smart Citation
“…A common removal half-time of 1 d is assigned to all four elements, based on the same data as considered in estimating the deposition fraction for bone surfaces, plus measurements of the early decline in whole-body retention of intravenously injected radioactive calcium, strontium, barium, or radium in human subjects (Spencer et al 1960;Bishop et al 1960;Heaney et al 1964;Harrison et al 1967;Phang et al 1969;Carr et al 1973;Likhtarev et al 1975;Malluche et al 1978;Henrichs et al 1984;Newton et al 1990Newton et al , 1991 coupled with measurements of soft-tissue retention as described earlier. A removal half-time of 1 d refers to the half-time that one theoretically would observe if recycling of activity to bone surfaces could be stopped.…”
Section: Icrp Modelmentioning
confidence: 99%
“…Based on data for human subjects injected with radioisotopes of calcium, strontium, barium, or radium (Spencer et al 1960;Bishop et al 1960;Heaney et al 1964;Harrison et al 1967;Phang et al 1969;Carr et al 1973;Likhtarev et al 1975;Malluche et al 1978;Henrichs et al 1984;Newton et al 1990Newton et al , 1991, it was concluded that the fraction of injected activity released from bone over the intermediate term (and thus assigned to exchangeable bone volume) is roughly one-sixth of activity leaving bone surfaces for all four elements.…”
Section: Icrp Modelmentioning
confidence: 99%